Analisis Penerapan Akuntansi pada UMKM Dilla Laundry di Kecamatan Pontianak Kota - septio, kahfi praditya (Jurnal KIAFE, 2024)
This study examines the application of accounting practices based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Dilla Laundry in Pontianak City. The study employs a descriptive qualitative approach with a case study design. Data were collected through structured interviews with the business owner. The results show that Dilla Laundry only maintains simple records of cash receipts and expenditures and has not prepared financial statements in accordance with SAK EMKM. The main constraints include the owner’s limited understanding of accounting and SAK EMKM, a preference for simple and practical records, the absence of properly archived transaction documents, limited human-resource competence in accounting, and insufficient government outreach and training. Therefore, the study applies the SAK EMKM framework by preparing an income statement, a statement of financial position, and notes to the financial statements. Regular financial recording and reporting are recommended to help the business monitor its financial condition, control cash inflows and outflows, evaluate performance, and support future business development.